Effect of post harvest quality management practices on fruit juices of small scale industries in Ghana: a case study of fruit juice producers in the Ashanti Region of Ghana - Ameyaw, Isaac (2017)
A thesis submitted to The Department of Horticulture, in partial fulfilment of the requirements for the degree of Master of Philosophy (Mphil Postharvest Technnology).